Bioactive Surfaces - Borner, Hans G.; Lutz, Jean-Francois; Badi, N. (Nezha) (Advances in polymer science, 2011)
Wischerhoff, Nezha Badi, André Laschewsky and Jean-François Lutz Smart Polymer Surfaces: Concepts and Applications in Biosciences * S. Petersen, M. Gattermayer and M. Biesalski Hold on at the Right Spot: Bioactive Surfaces for the Design of Live-Cell Micropatterns * Julien Polleux Interfacing Cell Surface Receptors to Hybrid Nanopatterned Surfaces: A Molecular Approach for Dissecting the Adhesion Machinery * Abigail Pulsipher and Muhammad N. Yousaf Self-Assembled Monolayers as Dynamic Model Substrates for Cell Biology * D. Volodkin, A. Skirtach and H. Möhwald LbL Films as Reservoirs for Bioactive Molecules * R. Gentsch and H. G. Börner Designing Three-Dimensional Materials at the Interface to Biology *   Joerg C. Tiller Antimicrobial Surfaces